Mengandaikan Budaya Teknologi Ramah Perempuan - Muhassonah, Izzuki (Musawa Jurnal Studi Gender dan Islam, 2007)
There are too many women and small groups that are left untouched by the government; it takes skill in science, especially in operating the machinery of communal economy. That is hoped for because women are not going to just stay at home and only worry about their family and always being subordinated by high technology culture. This phenomenon can still be tolerated; sadly word is still out in the newspapers, magazines, survey books and many researches that say that women still receive violence that are very diversified in motives and backgrounds. Violence to women is not only physical but also psychological, sexual, economical and the stealing of rights. That proves the existence of technological cultures that are women, unfriendly. Because of that, this article will try to discuss technological cultures that are not quite friendly or even hostile to women. Other than the discussion that focuses on that point, the main element that is targeted in this article is to think of how the current technology is upgraded to be women, friendly.